Environmental Chemistry: Asian Lessons - Bashkin, Vladimir N. (Springer Netherlands, 2003)
At present environmental chemistry is becoming an increasingly popular subject in both under graduate and graduated education in the whole World and especially in all Asian countries. Different courses in ecology, chemistry, environmental science, public health, geography, biology, and environmental engineering all include this subject in their curriculum. Many textbooks have appeared in recent years aiming to fulfill these requirements; however, most of these books operate mainly with examples from developed countries of Europe, USA and Canada. Taking into account the geographic boundaries of environmental pollution that is especially pronounced in Asia and the specific peculiarities of pollution in developing countries, this textbook is supposed to close the gap by providing regionally oriented knowledge in basic and applied environmental chemistry.